Endophytic Microbes Are Tools to Increase Tolerance in Jasione Plants Against Arsenic Stress - González-Benítez, Natalia; Martín-Rodríguez, Irene; Cuesta, Isabel; Arrayás, Manuel; White, James Francis; Molina, María Carmen (Frontiers in Microbiology, 2021)
Seed microbiota is becoming an emergent area of research. Host plant microbial diversity is increasingly well described, yet relatively little is known about the stressors driving plant endomicrobiota at the metaorganism level. The present work examines the role of horizontal and vertical transmission of bacterial microbiota in response to abiotic stress generated by arsenic. Horizontal transmission is achieved by bioaugmentation with the endophyte Rhodococcus rhodochrous, while vertical transmission comes via maternal inheritance from seeds. To achieve this goal, all experiments were conducted with two Jasione species. J. montana is tolerant to arsenic (As), whereas J. sessiliflora, being phylogenetically close to J. montana, was not previously described as As tolerant. The Jasione core bacterial endophytes are composed of genera Pseudomonas, Ralstonia, Undibacterium, Cutibacterium, and Kocuria and family Comamanadaceae across different environmental conditions. All these operational taxonomic units (OTUs) coexisted from seeds to the development of the seedling, independently of As stress, or bioaugmentation treatment and Jasione species. R. rhodochrous colonized efficiently both species, driving the endomicrobiota structure of Jasione with a stronger effect than As stress. Despite the fact that most of the OTUs identified inside Jasione seeds and seedlings belonged to rare microbiota, they represent a large bacterial reservoir offering important physiological and ecological traits to the host. Jasione traits co-regulated with R. rhodochrous, and the associated microbiota improved the host response to As stress. NGS-Illumina tools provided further knowledge about the ecological and functional roles of plant endophytes.